Heterotrophic Foraminifera Capable of Inorganic Nitrogen Assimilation - Bird, Clare; LeKieffre, Charlotte; Jauffrais, Thierry; Meibom, Anders; Geslin, Emmanuelle; Filipsson, Helena L.; Maire, Olivier; Russell, Ann D.; Fehrenbacher, Jennifer S. (Frontiers in Microbiology, 2020)
Nitrogen availability often limits biological productivity in marine systems, where inorganic nitrogen such as ammonium is assimilated into the food web by bacteria and photoautotrophic eukaryotes. Recently, ammonium assimilation was observed in kleptoplast-containing protists of the phylum foraminifera, possibly via the glutamine synthetase/glutamate synthase (GS/GOGAT) assimilation pathway imported with the kleptoplasts. However, it is not known if the ubiquitous and diverse heterotrophic protists have an innate ability for ammonium assimilation. Using stable isotope incubations (15N-ammonium and 13C-bicarbonate) and combining transmission electron microscopy (TEM) with quantitative nanoscale secondary ion mass spectrometry (NanoSIMS) imaging, we investigated the uptake and assimilation of dissolved inorganic ammonium by two heterotrophic foraminifera; a non-kleptoplastic benthic species, Ammonia sp., and a planktonic species, Globigerina bulloides. These species are heterotrophic and not capable of photosynthesis. Accordingly, they did not assimilate 13C-bicarbonate. However, both species assimilated dissolved 15N-ammonium and incorporated it into organelles of direct importance for ontogenetic growth and development of the cell. These observations demonstrate that at least some heterotrophic protists have an innate cellular mechanism for inorganic ammonium assimilation, highlighting a newly discovered pathway for dissolved inorganic nitrogen (DIN) assimilation within the marine microbial loop.